Cooperation within the supply chain : Inbound process development - Kukkonen, Ville (My University, 2021)
In order to efficiently manage a supply chain, several processes need to be aligned. Purchasing, logistics and warehousing all are part of a company’s inbound process. Decisions made at external suppliers can have impacts later in the process, at the warehouse or even later at the end customer. The inbound process needs to managed as a whole in order to have an efficient supply chain. Extensive cooperation is required internally between different teams, and externally within the supply chain network. This study looks into literature on supply chain management form different perspectives, SCM as a source of competitive advantage, cooperation within a supply chain, cooperation in partnerships and business networks, learning in a network context and supply chain risk management. This research was conducted using a qualitative research method. Semi-structured interviews were conducted in February 2021 at a case company and their external warehouse partner to gauge how the inbound process is managed and developed in cooperation with internal and external partners. The findings of the interviews are discussed and compared to the presented academic literature. Main findings of this study indicate that managing the inbound process requires cooperation, both internally and externally. The roles and responsibilities of each stakeholder need to be clearly aligned and communicated throughout internal and external partners. Organizational change is a major risk that can hinder process development. When going through organizational changes, companies should allocate sufficient resources to cope with the adaptation period.

Hallitakseen toimitusketjua tehokkaasti, useiden eri prosessien tulee toimia yhteistyössä. Osto, logistiikka ja varastointi ovat kaikki osia yrityksen sisään tulevan tavaravirran hallinnassa. Päätöksillä, joita tehdään ulkoisilla toimittajilla voi olla vaikutuksia toimitusketjun myöhemmissä vaiheissa, niin varastolla kuin jopa loppuasiakkaalla. Saapuvaa tavaravirtaa on hallittava kokonaisuutena, jotta koko toimitusketju säilyttää tehokkuutensa. Yhteistyötä vaaditaan niin sisäisten kuin ulkoisten kumppanien kesken. Tässä tutkielmassa käydään läpi akateemista kirjallisuutta koskien seuraavia aiheita: toimitusketjun hallinta eri perspektiiveistä, toimitusketju kestävän kilpailuedun lähteenä, yhteistyö toimitusketjun sisällä, yhteistyö kumppaneiden välillä ja verkostoissa, verkostoissa oppiminen ja toimitusketjun riskien hallinta. Tässä tutkimuksessa on käytetty kvalitatiivista tutkimusmetodia. Puolistrukturoidut haastattelut toteutettiin helmikuussa 2021 tutkimuksen kohteena olleessa yrityksessä ja heidän ulkoisella varastopartnerillaan. Haastatteluissa selvitettiin miten sisään tulevaa tavaravirtaa hallitaan kyseisessä yrityksessä, ja miten prosessia kehitetään yhteistyössä sekä sisäisten osapuolten, että ulkoisten kumppanien kesken. Haastattelujen tulokset esitellään ja niitä verrataan esitettyyn olemassa olevaan kirjallisuuteen. Tutkimuksen johtopäätökset ovat, että toimitusketjun hallinta vaatii yhteistyötä niin sisäisten kuin ulkoisten kumppanien välillä. Eri toimijoiden roolit ja vastuualueet tulee linjata selkeästi sekä kommunikoida kaikille osapuolille. Organisaatiomuutokset ovat suuri riski prosessien kehittämiselle. Yritysten tulee varmistaa riittävät resurssit organisaatiomuutosten läpikäynnin ajaksi.
Keywords: supply chains; organisational changes; networks (societal phenomena); cooperation (general); logistics; partnership; fi=Kansainvälinen liiketoiminta|en=International Business|; Master’s Programme in Strategic Business Development